Contact allergy to fragrance mix II and hydroxyisohexyl 3-cyclohexene carboxaldehyde: a retrospective study by international contact dermatitis research group - Bruze, Magnus; Ale, Iris; Andersen, Klaus E.; Cannavó, Alicia; Diepgen, Thomas L.; Elsner, Peter; Goh, Chee-Leok; Gonçalo, Margarida; Goossens, An; McFadden, John; Nixon, Rosemary; Puangpet, Pailin; et al. (Dermatitis, 2020)
Background - Fragrance mix II (FM II) is included in the baseline patch test series recommended by the International Contact Dermatitis Research Group (ICDRG). Hydroxyisohexyl 3-cyclohexene carboxaldehyde (HICC) is the most important sensitizer of the 6 fragrance materials included in FM II. Besides being a part of FM II, HICC is also tested separately in the ICDRG baseline series. - Objectives - The aim of the study was to investigate the prevalence of contact allergy to FM II and HICC in 2012-2016 with a focus on simultaneous reactions and the percentage of missed contact allergy to HICC provided that only FM II had been tested. - Patients and Methods - A total of 25,019 consecutive dermatitis patients in 13 dermatology clinics representing 12 countries in 5 continents were patch tested with FM II and HICC in the baseline series. - Results - Contact allergy to FM II and HICC was found in 3.9% and 1.6%, respectively. For FM II, the frequency varied from 1.5% to 7.6% in different centers. The corresponding range for HICC was 0.2% to 3.6%. Simultaneous contact allergy to FM II and HICC was noted in 1.4% with the range 0.2% to 2.6%. Seventy-seven patients (0.31%) with contact allergy to HICC did not test positively to FM II. The range for missed HICC allergy by testing only FM II in the different centers would be 0.04% to 0.74%. The ratio between the contact allergy rates for FM II and HICC was similar for all centers, except for Montreal having significantly more contact allergy to FM II than to HICC. - Conclusions - The frequency of missed contact allergy to HICC when testing only with FM II was less than 0.5%, therefore questioning the need to test HICC separately in the ICDRG baseline series.
Gesehen am 08.09.2020